Contrast-Enhanced Ultrasound: A Superior Method for Surveillance and Follow-up to Detect and Classify Endoleaks Following EVAR. Issue 4 (December 2020) - Hasan, Muhammad; Schiro, Brian J.; Benenati, James F.
Endovascular aneurysm repair (EVAR) has become the standard of care for many patients with abdominal aortic aneurysms. Because of the delayed complications associated with EVAR, namely the development of endoleaks, yearly surveillance of the endograft and aneurysm sac is required. Surveillance has traditionally been carried out with 3-phase computed tomography angiography of the abdomen and pelvis with the use of intravenous iodinated contrast. This incurs cumulative doses of radiation over the remainder of the patient's life and exposes these patients to repeated administrations of potentially nephrotoxic contrast agents. Contrast-enhanced ultrasound (CEUS) has emerged as an excellent method of evaluating and categorizing endoleaks without the use of radiation or nephrotoxic agents. This educational article centers around CEUS and its use in EVAR follow-up.